2017
DOI: 10.1016/j.msea.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Annealing behavior of a cast Mg-Gd-Y-Zr alloy with necklace fine grains developed under hot deformation

Abstract: The microstructure and texture development of a cast Mg-Gd-Y-Zr alloy during hot deformation and subsequent annealing were investigated by optical microscopy (OM) and electron backscattered diffraction (EBSD) technology. Initial microstructures with partially and fully developed new fine grains (NFGs), separately attended by continuous or interrupted hot forging, were various mixed grain structures composed of NFGs in necklace and retained coarse grains. It is shown that, during annealing, the development of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It was found that Mg alloys usually display typical features of CDRX during hot deformation [18][19][20][21][22], i.e., low angle boundaries were introduced due to the accumulation of dislocations, and then new fine grains were developed progressively from grain boundaries to grain interiors with the gradual increase in misorientation at sub-boundaries. Due to the lack of slip systems, twinning [22][23][24][25][26] and kinking [19][20][21][22] served as additional mechanisms for rapidly introducing large misorientations in deformation substructures and accelerating the formation of new fine grains. For the DRX behavior of CP-Ti, investigations [27][28][29] indicated that DRV was the dominant softening process for the annihilation of dislocation during high temperature deformation.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Mg alloys usually display typical features of CDRX during hot deformation [18][19][20][21][22], i.e., low angle boundaries were introduced due to the accumulation of dislocations, and then new fine grains were developed progressively from grain boundaries to grain interiors with the gradual increase in misorientation at sub-boundaries. Due to the lack of slip systems, twinning [22][23][24][25][26] and kinking [19][20][21][22] served as additional mechanisms for rapidly introducing large misorientations in deformation substructures and accelerating the formation of new fine grains. For the DRX behavior of CP-Ti, investigations [27][28][29] indicated that DRV was the dominant softening process for the annihilation of dislocation during high temperature deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The average KAM value of Mg-3Y-R sheet is found to be higher and drops from 1.57 to 0.38 remarkably after subsequent short-term annealing. Therefore, most of the areas nearly exhibit a strain-free state, indicating that SRX is a process of softening the work hardening effect [49,50]. The release of residual stress is beneficial to the improvement of ductility and stretch formability of Mg-3Y sheets.…”
Section: Microstructures and Micro-texture Evolution Of Alloy Sheetsmentioning
confidence: 99%
“…The KAM diagram is used to indicate the local dislocation density and strain degree in the microstructure. The darker the color, the greater the local misorientation [25]. The average local misorientation angles of the T0, T45, and T90 samples are 0.81, 0.87, and 0.76, respectively.…”
Section: Microstructurementioning
confidence: 99%